Joint together: The etiology and pathogenesis of ankylosing spondylitis - Xiong, Yuehan; Cai, Menghua; Xu, Yi; Dong, Peng; Chen, Hui; He, Wei; Zhang, Jianmin (Frontiers in Immunology, 2022)
Spondyloarthritis (SpA) refers to a group of diseases with inflammation in joints and spines. In this family, ankylosing spondylitis (AS) is a rare but classic form that mainly involves the spine and sacroiliac joint, leading to the loss of flexibility and fusion of the spine. Compared to other diseases in SpA, AS has a very distinct hereditary disposition and pattern of involvement, and several hypotheses about its etiopathogenesis have been proposed. In spite of significant advances made in Th17 dynamics and AS treatment, the underlying mechanism remains concealed. To this end, we covered several topics, including the nature of the immune response, the microenvironment in the articulation that is behind the disease’s progression, and the split between the hypotheses and the evidence on how the intestine affects arthritis. In this review, we describe the current findings of AS and SpA, with the aim of providing an integrated view of the initiation of inflammation and the development of the disease.